Geothermal Energy for Resilient Energy Systems: A Systematic Literature Review - Arif Atmoko; Rudy Laksmono; Novky Asmoro (IJBLE Scientific Publications Community Inc., 2026)
This systematic literature review investigates how geothermal energy contributes to energy resilience across electricity, heating, cooling, urban infrastructure, and industrial applications. Guided by PRISMA 2020, the review identified 365 Scopus records using geothermal- and resilience/sustainability-related terms. After filtering English-language journal articles published during 2015–2025 and screening titles, abstracts, full texts, and accessibility, 10 studies were included. Thematic synthesis identified four resilience pathways: dependable baseload and thermal supply; long-term resource stewardship through reinjection and thermal recharge; technological adaptability through ground-source heat pumps, aquifer modelling, hybrid systems, and repurposed wells; and economic-environmental robustness through lower emissions, reduced fuel-price exposure, and infrastructure reuse. Persistent constraints include high upfront costs, geological uncertainty, reservoir degradation, fragmented regulation, and limited social acceptance. Geothermal energy is therefore a strategic resilience asset, but its benefits depend on integrated technical, financial, institutional, and community-governance arrangements.